An unlikely Amish match - Chapman, Vannetta (Chapman, Vannetta. Indiana Amish brides., 2020)
Susannah Beiler is determined to protect the other young marriageable Amish women from falling for the new bad boy in town by pretending to date Micah Fisher herself! Their deal is simple: she<U+2019>ll keep him company if he stays away from her friends. It<U+2019>s not long before she starts to see there<U+2019>s more to Micah than his reputation...